Software-modeling complex SCSPS stream encryption algorithm - Білецький, Анатолій Якович; Навроцький, Денис Олександрович; Семенюк, Олександр Іванович (Ukrainian Information Security Research Journal, 2014)
Basis stream encryption algorithm SCSPS form Shannonprimitives nonlinear Substitution and Permutations primitives,as well as SP-networks, supplemented by primitivesof “moving coding” and stochastic cyclic Shift. Streamencryption is performed bitwise addition modulo 2 blocksciphered text size is 128, 192 or 256 bits, with equallength blocks of binary pseudorandom numbers (keys orgammas). Flow gammas produced a set of cryptographictransformations underlying secret encryption key. Modelingcomplex is subject to exclusion of one or more entitiesfrom the encryption algorithm. The analysis of efficiencySCSPS algorithm.